Youth as Agents of Peace : Somalia - World Bank; United Nations (World Bank, Washington, DC, 2018)
This paper is the first joint country study conducted by the United Nations and the World Bank aimed at translating into practice the principles of the United Nations Security Council (UNSC) Resolution 2250, through direct and local engagement with young people and their communities in one of the most fragile and conflict-ridden areas on the African continent. Focusing on young people is particularly meaningful as Somalia’s population is the youngest of the African continent overall. Against a backdrop of continued conflict, insecurity, and violent extremism facing Somalia, the study offers a positive vision for defining peace as articulated by young women and men. It concludes by offering an operational framework for supporting youth in peacebuilding. The report’s recommendations postulate a comprehensive understanding of youth, peace, and conflict going beyond solutions based solely on increased employment.